Contemporary survival outcomes of congenital systemic-to-pulmonary shunt in children with borderline pulmonary vascular resistant index compared to Eisenmenger syndrome - Nalin Chaiwangyen; Chodchanok Vijarnsorn; Paweena Chungsomprasong; Prakul Chanthong; Supaluck Kanjanauthai; Ploy Thammasate; Thita Pacharapakornpong; Densiri Bositthipichet; Jantaras Sengsim; Jarupim Soongswang; Teerapong Tocharoenchok; Ekarat Nitiyarom; et al. (Scientific Reports)
Abstract Pulmonary arterial hypertension (PAH) associated with congenital heart disease (PAH-CHD) is a complication that occurs after unrepaired significant systemic-to-pulmonary shunt. Treatment options for PAH-CHD-predominantly left-to-right (L-R) shunt in children with borderline-high pulmonary vascular resistant index (PVRi) have been debated. We aimed to assess the treatment and survival of children with PAH-CHD-predominantly L-R shunt with borderline to high PVRi, using Eisenmenger syndrome (ES) for comparison. In 1995–2021, a total of 142 patients with ES and 192 children with PAH-CHD-predominantly L-R shunt were eligible for our analysis. The PVRi in ES patients was 26.7 ± 16.8 WU m2. Most patients (91%) received PAH-targeted therapy. Of the 192 children with PAH-CHD-predominantly L-R shunt, the baseline PVRi was 9.2 ± 5.8 WU m2. A total of 64 patients (33.3%) had borderline PVRi (4–8 WU m2) and 98 patients (51%) had high PVRi (> 8 WU m2). Most patients (88.5%) responded to acute pulmonary vasodilatory testing and underwent repair, with 158 undergoing defect closure and 12 having fenestrated closure. A treat-and-repair strategy was used in 33 children (17.1%). The 10- and 15-year survival rates for patients with ES were 79.3% and 72.4%, respectively, which was significantly inferior to children with borderline PVRi [97.3% and 87.8% (p = 0.02)]; and high PVRi [91.6% and 89.5% (p = 0.06)], respectively. The survival rate of children receiving treat-and-repair was slightly higher than that of ES (p = 0.16). The independent mortality risk in children with PAH-CHD-predominantly L-R shunt was persistent PAH following the defect correction (adjusted hazard ratio 5.8, 95% CI 1.7–19.9, p = 0.005). Trial registration: TCTR20200420004.